The Empire Tweets Back? #HumanitarianStarWars and Memetic Self-Critique in the Aid Industry. (November 2019) - Chonka, Peter
In 2015, a series of memes appeared on Twitter under the hashtag #HumanitarianStarWars. Combining still images from the original Star Wars movies with ironic references to humanitarian/development jargon and institutions, the memes presented a humorous reflection on the modern aid industry. While memetic content has become an increasingly scrutinized area in digital culture studies—particularly with regard to unbounded and anonymous online communities, and popular discursive contestation—this article examines #HumanitarianStarWars to shed light on the possibilities and problematics of social media auto-critique undertaken by "insiders" in a particular professional realm. Keeping in mind critiques of the racial and imperial connotations of the (Western) pop-culture mythology itself, the article explores the use of the Star Wars franchise as a vehicle for commentary on an industry at work in the "Global South." It highlights an ambiguous process of meaning-making that can be traced through the memes' generation, circulation, and re-mediation. Although the memes provide a satirical self-reflection on practitioners' experiences and perspectives of power relations in the global development industry, certain tendencies emerge in their remixing of this Hollywood universe that may reinforce some of the dynamics that they ostensibly critique. The article argues that examination of the ideological ambivalence of an institutional micro-meme can yield valuable insights into tensions playing out in professional social media spaces where public/private boundaries are increasingly and irrevocably blurred.